РАЗВИТИЕ ЛОГИЧЕСКОГО МЫШЛЕНИЯ НА УРОКАХ МАТЕМАТИКИ КАК ОСНОВА ПОВЫШЕНИЯ КАЧЕСТВА ОБРАЗОВАТЕЛЬНОГО ПРОЦЕССА - Жандауова, Ш.Е.; Байтасова, А.В. (My University, 2019)
Аннотация Развитие логического мышления младших школьников – важная составная часть педа- гогического процесса. Помочь учащимся в полной мере проявить свои способности, развить инициативу, самостоятельность, творческий потенциал – одна из основных задач современ- ной школы. Abstract The development of logical thinking of younger students is an important part of the pedago- gical process. To help students to fully demonstrate their abilities, to develop initiative, independen- ce, and creative potential is one of the main tasks of the modern school.
Development of logical thinking in the lessons of mathematics as a basis for improving the quality of the educational process
Keywords: умственное воспитание; логика; мышление; полноценное развитие; mental education; logic; thinking; full development